Economic Empowerment: A Strategy to Address Gender based Violence (Journal of Gender and Social Issues, 2024)
This study examines the prevalent issue of gender inequality in material resources and its relationship to violence against women in Pakistan, focusing on Lady Health Workers (LHWs) in Karachi. The study uses a quantitative research approach and a survey research design to evaluate the status of working women in Karachi, especially LHWs. 200 participants completed a self-structured questionnaire that focused on demographic data, measures of economic empowerment, and violent situations at home. The findings show that LHWs have a complicated financial situation, even though they contribute to the family income. They also have serious difficulties saving money and owning a home. The results also highlight the startling prevalence of violence against women, as 20% of participants shared personal accounts of encounters. The survey highlights how important it is for lawmakers to take action in order to solve issues like equitable job opportunities, property rights, and violence against women.
Keywords: Access to Resources, Economic Empowerment, Gender Disparity, Lady Health Workers, Violence against Women